Efektivitas Pemberian Pupuk Organik Cair (POC) dari Limbah Kulit Pisang Kepok dan Kulit Mangga Terhadap Pertumbuhan Kangkung Darat (Ipomoea reptans) - Utami, Mega; Siska Dewi, Alfina; Hikmal Romadhon, Galih; Maharani, Maura; Andini, Putri; Naufal, Waliid; Idramsa, Idramsa; Febriyossa, Adelia (Universitas Cokroaminoto Palopo, 2025)
The excessive application of inorganic fertilizers in agriculture leads to environmental degradation, necessitating sustainable alternatives. This study evaluated the effectiveness of liquid organic fertilizer (LOF) formulated from banana peel, mango peel, and rice washing water on the vegetative growth of Ipomoea reptans. The research employed a Completely Randomized Design (CRD) with four treatment concentrations: 0 ml/L (control), 10 ml/L, 20 ml/L, and 30 ml/L, each replicated three times. Growth parameters assessed at 21 days after planting included plant height, number of leaves, number of roots, and fresh weight. Laboratory analysis revealed nutrient content of 0.04% nitrogen, 0.17% phosphorus, and 3.04% potassium, indicating a potassium-dominant formulation. The 10 ml/L treatment resulted in the highest plant height (18.00 cm), while the 30 ml/L treatment yielded the highest leaf number (9.33) and fresh weight (0.47 g). However, one-way ANOVA showed no statistically significant differences (p > 0.05) among treatments. The novelty of this research lies in utilizing a combination of commonly discarded household organic waste as a low-cost biofertilizer with measurable nutrient content. Although short-term results were statistically insignificant, the formulation demonstrates potential for refinement and longer application in sustainable agriculture